Echocardiographic evaluation of diastolic function in mouse models of heart disease. (January 2018) - Schnelle, Moritz; Catibog, Norman; Zhang, Min; Nabeebaccus, Adam A.; Anderson, Grace; Richards, Daniel A.; Sawyer, Greta; Zhang, Xiaohong; Toischer, Karl; Hasenfuss, Gerd; Monaghan, Mark J.; Shah, Ajay M.
Abstract: Background: Mouse models of heart disease are extensively employed. The echocardiographic characterization of contractile function is usually focused on systolic function with fewer studies assessing diastolic function. Furthermore, the applicability of diverse echocardiographic parameters of diastolic function that are commonly used in humans has not been extensively evaluated in different pathophysiological models in mice. Methods and results: We used high resolution echocardiography to evaluate parameters of diastolic function in mouse models of chronic pressure overload (aortic constriction), volume overload (aorto-caval shunt), heart failure with preserved ejection fraction (HFpEF; DOCA-salt hypertension), and acute sarcoplasmic reticulum dysfunction induced by thapsigargin - all known to exhibit diastolic dysfunction. Left atrial area increased in all three chronic models while mitral E/A was difficult to quantify at high heart rates. Isovolumic relaxation time (IVRT) and Doppler E/E′ increased significantly and the peak longitudinal strain rate during early filling (peak reverse longitudinal strain rate) decreased significantly after aortic constriction, with the changes being proportional to the magnitude of hypertrophy. In the HFpEF model, reverse longitudinal strain rate decreased significantly but changes in IVRT and E/E′ were non-significant, consistent with less severe dysfunction. With volume overload, there was a significant increase in reverse longitudinal strain rate and decrease in IVRT, indicating a restrictive physiology. Acute thapsigargin treatment caused significant prolongation of IVRT and decrease in reverse longitudinal strain rate. Conclusion: These results indicate that the combined measurement of left atrial area plus reverse longitudinal strain rate and/or IVRT provide an excellent overall assessment of diastolic function in the diseased mouse heart, allowing distinction between different types of pathophysiology. Highlights: Several echocardiographic indices of diastolic function are applicable to mouse models. Isovolumic relaxation time (IVRT) and peak strain during filling are easily quantified. Left atrial area increases with pressure and volume overload as well as HFpEF. Changes in IVRT and strain during filling distinguish restrictive physiology. Combined left atrial area and diastolic strain provide an ideal diagnostic framework.